Fürstensitz von Vix , Frankreich - Komp, Rainer (e-Forschungsberichte des DAI, 2023)
The German Archaeological Institute is supporting the international project „Vix et son environnement“ by executing surveys applying a vehicle driven high resolution, large scale geomagnetic system. The aim is to investigate the surroundings of the princely site of Vix, dated to the Hallstatt and La Tène era to get an idea of the contextual landscape. Establishing this method in the last three years, prehistoric and historic as well as recent and geological features were discovered. An area of nearly 200 ha was prospected. Detailed views of tumuli as well as new traces of further graves were identified. Among others, gallo-roman villae and even a small late roman settlement enhance the knowledge of greater Vix.